Contemporary X-ray electron-density studies using synchrotron radiation. (2014) - Jørgensen, M. R. V.; Hathwar, V. R.; Bindzus, N.; Wahlberg, N.; Chen, Y.-S.; Overgaard, J.; Iversen, B. B.
No abstract available